Two-step facile fabrication of a superamphiphilic biomimic membrane with a micro–nano structure for oil–water emulsion separation on-demand. (7th July 2022) - Zeng, Qinghong; Qiu, Lei; Zhao, Siyang; Zhang, Jiaxu; Huang, Jinxia; Guo, Zhiguang
Abstract : A smart separation membrane with super-amphiphilic wettability was fabricated by a simple two-step method. The separation efficiency of the membrane towards the emulsion is more than 99.6%, and it can be recycled. Abstract : Superamphiphilic materials have attracted much attention due to their different wettability in different media. Through a simple two-step method, we fabricated a smart separation membrane with super-amphiphilic wettability. Under the action of a micro–nano structure and fine pore size, the target emulsion can be separated under pre-wetting conditions. After testing, the separation efficiency of the membrane towards the emulsion is more than 99.6%, and it can be recycled. The membrane has a potential role in dealing with the increasingly serious pollution problem.